The parasitoid Closterocerus chamaeleon has a greater development and survival rate than of its hosts, the Eucalyptus gall wasps Ophelimus eucalypti and Ophelimus maskelli in Sumatra, Indonesia. (22nd July 2021) - Hanjelina Br Sinulingga, Nike Grace; Tarigan, Marthin; de Souza Tavares, Wagner; Ansor, Khairul; Pasaribu, Irfan; Koda Kkadan, Srikumar; Angaini Panjaitan, Ria; Dewi Puspita, Kinanti; Israel Muro Abad, Jupiter; Duran, Alvaro
Abstract: Ophelimus eucalypti and Ophelimus maskelli are gall wasps that are considered as a threat to the large Eucalyptus commercial plantations in Sumatra, Indonesia. However, they are partially suppressed by parasitoids including Closterocerus chamaeleon . The aim of this study was to evaluate the longevity and daily survival rate of O. eucalypti, O. maskelli and C. chamaeleon adults when receiving or not receiving food sources and also when reared in four different vial types under two environments (one environmentally controlled and another ambient), in a laboratory in Riau, Sumatra. The rearing test of C. chamaeleon as a biocontrol agent would be used for augmentative releases. We also evaluated the duration of the stages and the complete lifespan (egg → larva → pupa → adult) of O. eucalypti in a greenhouse in Porsea, North Sumatra, Indonesia, where this species is aggressive. With few exceptions, the longevity and survival rate of O. eucalypti, O. maskelli and C. chamaeleon adults was similar between the two conditions. The longevity and survival of C. chamaeleon were much greater than those of its gall wasp hosts, and of O. eucalypti greater than that of O. maskelli . Overall, these parameters were greater for gall wasps and the parasitoid reared in the larger vial types. The food source provided to O. maskelli adults did not however benefit the longevity of this gall wasp in the best tube type. The lifespan of O. eucalypti (mean ± SD of the mean) was 44 ± 6 days in a greenhouse. The much greater longevity and survival rate of C. chamaeleon than those of its hosts are facts that trigger the success of this insect as a gall wasp parasitoid. The higher longevity and survival of O. eucalypti compared to O. maskelli contribute to the higher threat status of O. eucalypti to Eucalyptus . Abstract : The gall wasp and the parasitoid adults can be reared in the larger vial types for a greater longevity period. The longevity and survival of C. chamaeleon are possible driving forces to the success of this insect as a gall wasp parasitoid. The greater longevity and survival of O. eucalypti may contribute to the higher threat status of this gall wasp species in Sumatra.